Establishment of dry-chemistry-based reference intervals of routine liver function tests for the adult population of Gandaki Province, Nepal. - Asmita Sharma; Daya Ram Pokharel; Ganesh Dhakal (Public Library of Science (PLoS), 2024)
Every clinical laboratory should ideally establish its own population-specific reference intervals (RIs) to promote precision and evidence-based medicine. However, clinical laboratories in Nepal find it easier to follow external RIs than establish their own, leading to a lack of RIs specific to the local population. This study thus aimed to establish RIs of routine LFTs for the adult population of Gandaki Province, Nepal, and compare them with the current RIs used by our laboratory. We established the dry-chemistry-based reference intervals of 11 common LFT parameters for the adult population of Gandaki Province, Nepal using the direct priori-based method. The combined and sex-specific 95% double-sided RIs of total protein, albumin, globulin, A/G ratio, bilirubin, aspartate aminotransaminase (AST), alanine aminotransaminase (ALT), AST/ALT ratio, and alkaline phosphatase (ALP) were established using non-parametric percentile method. The new RIs were also compared with the currently used RIs that were adopted from the reagent kit inserts. The newly established RIs for each LFT were: Total proteins: 68.0-69.0g/L, albumin: 39.0-52.0g/L; globulin: 27.0-42.0g/L; A/G ratio: 1.1-1.8; total bilirubin: 5.13-25.65μmol/L (0.30-1.50mg/dl); unconjugated bilirubin: 1.71-17.10μmol/L (0.10-1.00mg/dl); conjugated bilirubin: 0.00-10.26 μmol/L (0.00-0.60mg/dl); AST: 20.0-43.2U/L; ALT: 11.0-53.0 U/L; AST/ALT ratio: 0.7-2.1; ALP: 42.0-135.4U/L. The RIs of albumin, globulin, A/G ratio, AST, ALT, and AST/ALT ratio differed significantly (p < 0.05) between males and females. Moreover, calculated out-of-range values showed that up to 4-40% of apparently healthy adults were classified as having abnormal test results based on current RIs. The newly established RIs fulfil the need for population and platform-specific RIs for the adult population of Gandaki Province of Nepal and bring more conformity and accuracy in interpreting the LFT results, diagnosis of hepatobiliary diseases, clinical decision-making, monitoring the success of therapy and future liver specific biomedical researches within the Gandaki Province of Nepal.